Characterizing the Drug-Release Enhancement Effect of Surfactants on Megestrol-Acetate-Loaded Granules - Gábor Katona; Bence Sipos; Rita Ambrus; Ildikó Csóka; Piroska Szabó-Révész (MDPI AG, 2022)
In this study, the effect of Cremophor® RH 40 (CR 40) classic micelles and Soluplus® (SP) polymeric micelles were investigated on a novel granule-type drug-delivery system containing megestrolacetate (MGA). Using a risk assessment-based approach on the formulation via melt technology resulted in the formation of these granules, presented as the dosage, with proper particle size and flow characteristics. Due to the application of a eutectic carrier base composition, gentle process conditions were reached, retaining the crystalline structure of the carrier system and allowing for the proper distribution of MGA in the granules. The increased water solubility (0.111 mg/mL to 2.154 mg/mL), and the decreased nano particle size (102.27 nm) with uniform distribution (polydispersity index of 0.259) and colloid stability (zeta potential of −12.99 mV) resulted in SP polymeric micelles prevailing over CR 40 micelles in this gastric dissolution study, performed in biorelevant fasted and fed state drug-release media. Mathematical characterization and kinetic model fitting supported the fast drug-release mechanism of polymeric micelles over micelles. The value-added polymeric micelle-containing formulation developed can be successfully administered perorally and the enhanced drug release offers the possibility of greater drug absorption in the gastrointestinal tract.